2018
DOI: 10.1387/ijdb.170283jh
|View full text |Cite
|
Sign up to set email alerts
|

The early development of germ cells in chicken

Abstract: Primordial germ cells (PGCs) are the founder cells for mature gametes, the vehicles by which individuals transmit genetic and epigenetic information to later generations. Since the 19 century, avian species (chickens in particular) have been widely used for germ cell research. Previous studies have used chicken PGCs for a variety of research applications, including as a model for studies focusing on germline development. Other applications of chicken PGCs, including conservation efforts for avian species and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 106 publications
0
26
0
Order By: Relevance
“…From E15 to E26, the ovarian cortex becomes more thickened, and moreover, germ cells differentiate into primary oocytes with an enlarged volume and form more oocyte nests (Figure 1). In particular, since PAS can efficiently stain glycogens that are abundant in the cytoplasm of germ cells and CVH is recognized as the most reliable germ cell marker (Kim and Han, 2018), both PAS staining and immunohistochemical staining with CVH were used to reveal changes in the number of germ cells during late geese embryonic development. It was observed that the total number of primary oocytes within the nests decreases from E15 to E26 (Supplementary Figure S1).…”
Section: Histomorphological and Immunohistochemical Changes During Eamentioning
confidence: 99%
“…From E15 to E26, the ovarian cortex becomes more thickened, and moreover, germ cells differentiate into primary oocytes with an enlarged volume and form more oocyte nests (Figure 1). In particular, since PAS can efficiently stain glycogens that are abundant in the cytoplasm of germ cells and CVH is recognized as the most reliable germ cell marker (Kim and Han, 2018), both PAS staining and immunohistochemical staining with CVH were used to reveal changes in the number of germ cells during late geese embryonic development. It was observed that the total number of primary oocytes within the nests decreases from E15 to E26 (Supplementary Figure S1).…”
Section: Histomorphological and Immunohistochemical Changes During Eamentioning
confidence: 99%
“…Bearing in mind the mechanisms of epigenetic changes in PGCs [ 19 , 31 ] and factors affecting the molecular stability and fate of cultivated PGCs, further marker-assisted assays will be applied to our in vitro systems, followed by in vivo validation of the function of retained PGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it cannot be definitely determined which PGC type should be preferred over another to successfully achieve various technological goals. Kim and Han [ 19 ] emphasize a need to gain a deeper knowledge of epigenetic mechanisms, which might be affected not only by the culture conditions but also by somatic factors of recipient surrogates. Marker-assisted sorting techniques have been developed to fractionate PGCs from the isolated cell cohorts and can be used for both gPGCs and cPGCs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, chickens have played a vital role in animal research as alternatives and outbred experimental species to humans to compensate for ethical constraints [2][3][4]. It works especially well when isolating and gaining a considerable number of pluripotent embryonic stem cells (ESCs) and primordial germ cells (PGCs) is much easier and convenient in chickens than other species due to the in ovo embryonic development [5,6]. This unique advantage accelerates the application of chicken ESCs and PGCs in studying the mechanism of human germ cell development and differentiation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In chickens, ESCs have been derived from cultures of chicken blastoderms taken from stage X-XII and PGCs can be obtained from the genital ridge (the precursor of gonad) at stage 28-30 embryos [6,11]. ESCs (blastoderms) represent the earliest accessible post-laying developmental stage prior to primitive streak formation and gastrulation; PGCs (genital ridge) represent the time when gonads are still morphologically identical in each sex ("bipotential") [12,13].…”
Section: Introductionmentioning
confidence: 99%